KILKA UWAG NA TEMAT ROLI III STATUTU LITEWSKIEGO W WYKŁADZIE PRAWA KRAJOWEGO NA PRZEŁOMIE XVIII I XIX WIEKU - Godek, Sławomir (Zeszyty Prawnicze, 2016)
Some Remarks on the Role of the Third Statute of Lithuania in Courses on National Law at the Turn of the Nineteenth Century Summary The long-term validity of the Third Lithuanian Statute of 1588 is a factor often highlighted in the scientific literature devoted to the history of the Lithuanian-Russian lands. The two and a half centuries that the codex operated have left a lasting imprint on the legal relations of these vast territories. In Belarusian lands once belonging the Republic and separated from it by the First Partition, the Statute was abolished as a consequence of the repression after the November Uprising in 1831. In the western and south-western guberniyas, the Statute survived somewhat longer; it was repealed in 1840. In academic circles, both Polish and international, the post-Partition fate of the Lithuanian codex has not yet been clarified. It seems that one aspect which is worth paying attention to in studies on the condition of the Statute after the Partitions is its role in the teaching of law in the late eighteenth and early nineteenth centuries. Surviving sources, in form of the lecture courses, students’ notes, reports intended for educational authorities and examination tables leave no doubt that the Statute of Lithuania was the very basis of national law lecture courses, both at the University of Vilnius, as well as at the High School and then Lyceum in Kremenets and the Academy of Polotsk. In the lectures of Adam Powstański, Ignacy Danilowicz, Aleksander Korowicki, Józef Jaroszewicz, Ignacy Ołdakowski, and Aleksander Mickiewicz, the Statute was always depicted as one of the most important sources of national law, which maintained its currency, and whose provisions were cited most frequently to illustrate the legal institutions under discussion.